Assessment of the prevalence and severity of Diabetic Retinopathy in Type 2 Diabetes mellitus in retina department of Lumbini Eye Institute and Research Center: A Cross-sectional study - Bishnu Prasad Nau; Ramesh Chandra Giri; Dikshya Khadka; Chandrajeet Kumar Yadav; Raman Kumar Gurmaita (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: One of the most dangerous microvascular effects of diabetes mellitus is diabetic retinopathy, which harms the blood vessels that supply the light-sensitive tissue in the rear of the eye. The changing pattern of lifestyle and advancement of technology, type 2 diabetes mellitus has become more common. Thus, this study was aimed to determine the prevalence and severity of diabetic retinopathy in individuals with type 2 diabetes who visited the Lumbini Eye Institute and Research Center retina department. Results: It was found that 115 of the 725 participants in the study had type 2 diabetes. The average age of participants was found as 54.6 ±8.889 years. Among 115 type 2 diabetic patients, 15.86% of participants were observed having diabetic retinopathy. The 34.8% of participants had history of less than five, and 65.2% had history of more than five years, of type 2 diabetes. The prevalence of diabetic retinopathy was more common in men than in women. Out of the 230 eyes, 57.82% had diabetic maculopathy, 20.9% had proliferative diabetic retinopathy, 7.4% had Advanced Diabetic Eye Disease, and 8.7% had non-proliferative diabetic retinopathy. Conclusion: The present study found that people with type 2 diabetes had a higher prevalence and severity of diabetic retinopathy with a higher male-to-female ratio.